A 7.5-GHz Frequency-Hopping CDMA UWB Transceiver for Secure Multi-Sensor Connectivity - Lin, Luhua; Wang, Bowen; Rhee, Woogeun; Wang, Zhihua (IEEE transactions on circuits and systems. II, Express briefs, 2025)
This brief describes an ultra-wideband (UWB) transceiver architecture that employs a frequency-hopping code-division multiple-access (FH-CDMA) scheme for secure multi-sensor connectivity with up to 18-channel capacity. By using distinct frequency-hopping (FH) patterns based on m-sequence, quantitative analysis and simulation results show that the FH-CDMA UWB system can support up to 18 users simultaneously sharing the same transmission band. The duty cycle control of a carrier signal for each FH cycle enables the transmitter to perform baseband clock synchronization with nano-second resolution. A prototype 7.5-GHz UWB transceiver is implemented in 65-nm CMOS. With the FH enabled, the transmitter meets the UWB spectrum mask. The receiver achieves a sensitivity of -91 dBm at 25 kb/s and exhibits <1-dB degradation when three users transmit signals simultaneously.